The Nietzschian typologie - da Silva, Vagner (2008)
This article is one of the results of master’s degree research, whose dissertation had for title “Nietzsche’s great politics, a moral of the irresponsibility”. The research analyzed the relationship between morals and politics in Nietzsche’s thought, based on three commentators of his thought: Ansell-Pearson, Walter Kaufmann and Müller-Lauter. In this work we concluded that Nietzsche’s political thought only takes place as educational project; in reason of that, we analyzed the proposals of his education in the last chapter of the referred dissertation, entitled “The education for the great politics”, in which we verified the importance of the human and literary types used by Nietzsche to illustrate his ideas. We propose in this article to analyze the diversity typologies created and used by the thinker – the strong and the weak ones – and its relationship with the education, afterwards will be shown what characterizes each one of them and the way the will, the power and the resentment are shown in both.